Dimensionamento e estimativa dos custos de um sistema de tratamento de águas cinzas para fins de reuso na irrigação - BAIA, Cintia Alves (2019)
This work presents a design for the design of a gray water reuse system for irrigation, contemplating definitions that meet the parameters established in the Brazilian Technical Standards Association (BTSA) recommendations NBR 7229/92, NBR 7229/93, NBR 13969/97 and NBR 8160/99. The project was carried out to be implemented in a low-cost, single-family rural residence located at the Três Torres vicinal, at 8 km from the municipality of Breu Branco, Pará. The type of treatment system used was based on an experiment carried out in the municipality of Mossoró, Rio Grande do Norte, taking into account the economic viability of the implantation and maintenance. Gray water collection will take place in various parts of the residence (wash basin, wash basin, washing machine, washing machine and kitchen sink). Quantitative and qualitative characterizations were based on the literature. The pretreatment stage of the water from the kitchen sink, is composed of a box of masonry grease in cylindrical format with dimensions of 40 cm in diameter and 50 cm in height. To complement the treatment we will have: a septic tank with a capacity of 2000 L and an anaerobic filter of 800 L. In the disinfection step was adopted the use of a simplified chlorinator, being an alternative of easy operation. Finally, the storage of the treated water will have a lower reservoir of 1000 L and with the aid of a BP500 peripheral pump, sent to a 1000 L backwater reservoir, so the reuse water will be distributed by gravity to irrigate plants ornamental and non-fruiting. The purpose of the study is to generate information that aims to motivate the implementation of new gray water reuse projects in rural residences, from an economically viable experiment that transforms the water that would be discarded becoming an agent polluting the environment in water of reuse.